Antifragile : things that gain from disorder - Taleb, Nassim Nicholas, 1960- (New York (N.Y.) : Random House, 2012)
Nassim Nicholas Taleb, the bestselling author of The Black Swan and one of the foremost thinkers of our time, reveals how to thrive in an uncertain world. Just as human bones get stronger when subjected to stress and tension, many things in life benefit from stress, disorder, volatility, and turmoil. What Taleb has identified and calls antifragile are things that not only gain from chaos but need it in order to survive and flourish. In The Black Swan, Taleb showed us that highly improbable and unpredictable events underlie almost everything about our world. Here Taleb stands uncertainty on its head, making it desirable, even necessary. The antifragile is beyond the resilient or robust. The resilient resists shocks and stays the same; the antifragile gets better and better. What's more, the antifragile is immune to prediction errors and protected from adverse events. Why is the city-state better than the nation-state, why is debt bad for you, and why is what we call "efficient" not efficient at all? Why do government responses and social policies protect the strong and hurt the weak? Why should you write your resignation letter before starting on the job? How did the sinking of the Titanic save lives? The book spans innovation by trial and error, life decisions, politics, urban planning, war, personal finance, economic systems and medicine, drawing on modern street wisdom and ancient sources. Antifragile is a blueprint for living in a Black Swan world. Erudite, witty, and iconoclastic, Taleb's message is revolutionary: the antifragile, and only the antifragile, will make it. Nassim Nicholas Taleb has devoted his life to problems of uncertainty, probability, and knowledge and has led three careers around this focus, as a businessman-trader, a philosophical essayist, and an academic researcher.
Keywords: Antifragiel; Wetenschap; Wetenschapsfilosofie